Artificial Intelligence and Health Information Literacy (Journal of EAHIL, 2025)
The proliferation of generative AI is changing health information behaviour. But the problems of accuracy and lack of transparency it has require users to develop some degree of AI literacy as an aspect of their health information literacy. There are many models of AI literacy suggesting key potential components such as knowledge of AI technologies; how to use them and evaluate outputs; how to protect one’s own safety; and ethical awareness, including of wider societal impacts. Conceiving these components as making up AI competency implies that it consists of the persistent attitudes and values of a critical information user, not the satisfied consumer that generative AI models try to create.